Associations between health-related quality of life and health care costs among children with atopic dermatitis and their caregivers: a cross-sectional study - Olsson, Maja (2022)
Atopic dermatitis is associated with a decreased health-related quality of life and contributes to substantial health care costs. It is important to understand what accelerates health care costs to inform various stakeholders, so they can effectively meet health care needs. This cross-sectional study aims to explore associations between health-related quality of life, health care costs, and cost-accelerating variables.